TWO NEW BINARIES AND CONTINUING OBSERVATIONS OF HUNGARIA GROUP ASTEROIDS - Warner, Brian D. (Minor Planet Bull, 2015)
Analysis of CCD photometry for five asteroids lead to the discovery of two new binary objects. (190208) 2006 AQ, is a rare “wide binary” example with a primary period of 182 h and secondary period of 2.62002 h. 2014 WZ120 is a near-Earth asteroid with a primary period of 3.361 h and orbital period of 13.665 h. The estimated effective diameter ratio for the pair is Ds/Dp ≥ 0.32. The other three asteroids, 1103 Sequoia, 2083 Smither, and 3880 Kaiserman, all members of the Hungaria group, show varying signs of a secondary period but no mutual events that would confirm the existence of a satellite.